ANALISIS KOMPETENSI PROFESIONAL GURU SEKOLAH DASAR NEGERI GUGUS II KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Peni Darmawan; Eddy Noviana; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this research was to determine the professional competence of the State Primary School Teachers' Cluster II Marpoyan Damai District Pekanbaru. This type of research was descriptive with quantitative approach that provides an overview of the state of progress on the object of research was analysis of Professional Competence State Primary School Teachers Cluster II Marpoyan Damai District Pekanbaru. The sample was used in this research that teachers are stratified S1 as many as 46 teachers. The research instrument used in the form of a questionnaire. The research was concluded that the professional competence of public elementary school teachers Cluster II Marpoyan Damai District Pekanbaru overall indicator reached 58.96% with a good enough category.Key Words: Teacher Professional Competence